Effect of temperature on meiosis in Scots pine plus trees with meiotic mutations and chromosome rearrangements in their genomes - Mytrochenko, V. V. (Forestry and Forest Melioration, 2020)
Introduction The global climate warming can affect the vegetative growth and generative development of pine forests to the south of 54° N. lat. (Reich & Oleksyn. 2008). The generative sphere of Scots pine (Pinus silvestris L.) is most temperature-sensitive, especially the meiosis of microsporogenesis. A higher temperature has low mutagenic effect; however it can strengthen effect of other mutagens such as ionizing radiation, ultraviolet rays, and chemicals. For example, a temperature raise brought about an increased frequency of chromosomal aberrations in meiosis of microsporogenesis in pine trees in contaminated areas after the Chernobil accident (Mytrochenko & Shlonchak 2004). Apart from external mutagens, a Scots pine has genetic factors that cause aberrations at meiosis of micro- and macrosporogenesis: meiotic gene mutations and chromosomal rearrangements. In some Ukrainian regions, up to 28% of Scots pine plus trees contain these genetic factors in genomes (Mytrochenko 2004, 2006). The aim of the study was to investigate how temperature influences the frequency of typical aberrations in meiosis in Scots pine plus trees with meiotic mutations and chromosomal rearrangements. Materials and Methods The study was carried out in the year 2003 (with the average daily temperature during meiotic divisions (1–7 May) of 15.8°С) and in the year 2004 (with the average daily temperature during meiotic divisions (23–30 April) of 10.8°С). Fourteen clones of plus trees with a different meiotic mutations and chromosomal rearrangements were selected in the Scots pine clone bank located in the Staropetrivske Forestry in the State Enterprise “Kyiv Forest Research Station”. The meiotic gene mutations were ps + tps (1 clone), ms43 (3 clones), ds І (2 clones), ds ІІ (2 clones). The chromosomal rearrangements were: inversion (In) – 5 clones and translocation (Tr) – 1 clone. During the meiotic divisions, microstrobiles from the each clone were collected every day and fixed in 3:1 ethyl alcohol-acetic acid for 24 hours and then stored in 70% ethyl alcohol in a refrigerator. The meiotic divisions were studied in a temporary squash preparations stained in hematoxylin according to the methods of Shoferystova (1973). The slides were examined with the “Biorex-2” microscope with a magnifying power of 40 ? 15 and 40?7; microphotography was done with the Cаnon A310 camera. We studied 500 microsporocytes for ana-telophase in both meiotic divisions. Among them, a percentage of microsporocytes with typical aberrations for each meiotic mutation and chromosomal rearrangement were determined. A difference in parts of microsporocytes with deviations was determined by t-criterion (Lakin 1990) Results Meiotic gene mutations. Mutations ps + tps and ms43 disturb a structure and function of the spindle apparatus in the meiotic cells. Both mutations are monogenic and recessive, they occur in microsporogenesis only. Mutation ps+ tps involves formation of two pollen grains and a parallel spindles orientation at the second meiotic division with their following fusion on both ends (ps) or one end (tps). The spindle fusion was observed in 4.4% of microsporocytes in warm 2003 only. Cytologic picture of mutation ms43 was evident as randomly scattered chromosomes in a cell or uneven distribution among several poles in cause of spindle splitting at A I, with further formation of polyads instead of dyads and tetrads. The average percentage of microsporocytes with typical for ms43 aberrations was 5.1% in warm 2003 and 4.3% in cold 2004. However, the study did not show a significant difference between them by t-criterion. The mutation has a photoperiodic sensitivity (Peremyslova 2006). Desynaptic mutations ds disturb the chiasmata formation as a result of untimely synaptonemal complexes destruction leading to the appearance the univalents in M I and chromosome lagging in A I-II. Desynaptic mutations are divided into two groups (ds І and ds ІІ) by the ability of centromeres of sister chromatid to separate at A I (ds ІІ) or not separate (ds І). The mutations are monogenic and recessive; at that, they occur in macro- and microsporogenesis. Both the ds І and the ds ІІ are temperature-sensitive. On the average, in ds І mutants, the proportion of the microsporocytes with lagging chromosomes was 5.6% in warm 2003 and in only 2.3% in cold 2004. On the contrary, in ds ІI mutants, 4.7% of the microsporocytes with lagging chromosomes were found in cold 2004 and 1.4% in warm 2003. The difference between the yearly average percentages of the aberrant microsporocytes was reliable for t-criterion with the 5% of confidence level for the both mutations. The chromosomal rearrangements. Inversions. At meioses we can observe only large heterozygous paracentric inversions, when there is synapsis of homologous segments resulted from the formation of an inversion loop. Crossing over within the loop produces acentric fragments and chromosome and chromatid bridges, which can be observed in A I-II. In clones with inversions, 11.4% of the aberrant microsporocytes were found in 2003 and only 3.7% in 2004. Translocation is a mutual exchange of terminal segments from the arms of two non-homologous chromosomes. At meiosis, when a heterozygous translocation is present, during pairing of homologous chromosome segments, followed by crossing-over, translocations may form a tetravalent, and rings of 4 chromosomes are formed at M I. If the pairing does not take place, there are open bivalents in М I. In 2003, only open bivalents were noticed while in cold 2004, the rings of four chromosomes were observed in 19.2% of the microsporocytes studied in metaphase. Probably, frequency of unbalance gametes formation depends on the tetravalent presence or absence as this clone has year-to-year variation of underdeveloped pollen grains and seed buds number. Conclusions The generative sphere of most studied Scots pine plus trees with the mei-genes mutations and chromosomal rearrangements in their genomes has an increased temperature-sensitivity during meiosis in the process of microsporogenesis. Among the mei-genes mutations which disturb the structure of the spindle fission (ps + tps and ms43) considerable temperature dependence was detected in ps + tps. A change in the temperature regime did not influence the mеi-gene mutant ms43 expression. The mutant mei-genes that control certain processes of synapsis and recombination (ds І, ds ІІ) and chromosomal rearrangements (inversions and translocations) have an increased temperature-sensitivity. At that, the aberrations quantity caused by them depends on the processes of synapsis and recombination. In the trees with inversions, the part of aberrant microsporocytes increased when a temperature raised, and in those with translocation, the tetravalents formation was observed when temperature decreased. A large number of plus trees with the mei-genes mutations and chromosomal rearrangements in their genomes in certain regions suggests an idea that they contain particular genetic factors, which give them an advantage in growth due to their high competitive abilities in optimal conditions or resilience in unfavourable ones. Therefore, these trees can be recommended to use when creating seed orchards. Scots pine plus trees with mei-genes mutations and chromosome rearrangements should be thoroughly studied in clone archive plantations, and their progeny should be actively used in subsequent breeding programmes. 4 Figs., 1 Table, 23 Refs. Key words: Scots pine, microsporogenesis, meiosis, meiotic gene mutations, chromosomal rearrangements, temperature sensitivity.